FOREWORD - GURGU, Elena (Annals of Spiru Haret University. Economic Series, 2019)
In their article called The New Economy Drivers and Disrupters Report. Tracking the Forces Threatening the World’s Hottest Economies published in Bloomberg Businessweek in October 29, 2019, authors Tom Orlik, Scott Johnson and Alex Tanzi say that “twenty years ago, China’s economy was a tenth the size of the United States. In 2019, it is two-thirds as big. In 2039, on the current trajectory, it will be more than 10% bigger. India will have leapfrogged Japan and Germany to claim the No. 3 spot in the global rankings. Vietnam will be closing in on the top 20.  Disruptive forces are sweeping the global economy. Populist regimes are throwing out the policy rulebook. Protectionism is deadening the trade flows that drove China’s rise. Automation and the digital economy are boosting productivity for some, eroding old sources of advantage for others. The threat of climate change looms. The path to prosperity followed by such success stories as Korea and Japan is increasingly hard to follow. From Beijing to Brasilia, getting the right mix of smart investment, skilled workforce, innovation capacity and effective governance in place is already tough to do. Combating disruptive forces – which, from protectionism to climate change, threaten an outsize impact on low- and middle-income economies – adds to the challenge.” The same Report says that “the origins of many of the changes sweeping the global economy can be traced to two sources: trade and technology. .....